Chapter 2 First Contacts, Slavery and Kinship in North-Eastern Amazonia - Grotti, Vanessa (Berghahn Books, 2016)
The first book to address the classic anthropological theme of property through the ethnography of Amazonia, Ownership and Nurture sets new and challenging terms for anthropological debates about the region and about property in general. Property and ownership have special significance and carry specific meanings in Amazonia, which has been portrayed as the antithesis of Western, property-based, civilization. Through carefully constructed studies of land ownership, slavery, shamanism, spirit mastery, aesthetics, and intellectual property, this volume demonstrates that property relations are of central importance in Amazonia, and that the ownership of persons plays an especially significant role in native cosmology.